Elderly care by village health volunteers during COVID-19 pandemic in Thailand - Sumiar, Haening Ratna; Viwatpanich, Kanvee (BKM Public Health and Community Medicine, 2024)
Purpose: This study aimed to understand how village health volunteers (VHV) perform their duties and look after older adults during the COVID-19 pandemic health crisis. Methods: We used in-depth interviews, group interviews, and observation to collect the data. This study was carried out in Wat Rong Lot, Chiang Rai, Thailand. Eleven people were involved in this research including one Public Health Department officer, Master of the Temple, five VHVs, one nurse, and three older adults in the community. We used content analysis to analyze our data. Results: Before the pandemic, VHV’s duties included health screening and monitoring, reporting the results to the primary health center, and health education to the older adults in the community. During the pandemic, they perform these duties by making a monthly visit to conduct ADL and living arrangement assessment and drug delivery. Since the lockdown, many VHV duties must be shifted which resulted in pausing regular care plans for the elderly. However, VHVs keep delivering health services to the elderly by making home visits in case of an emergency, drug delivery, and donating masks and medical supplies. They were burdened with additional responsibilities related to COVID-19 prevention, detection, and surveillance. They admitted to facing some challenges such as being unconfident when performing their work and distrust from the community. Conclusion: The additional responsibilities and lockdown hinder regular treatment. Further research is needed regarding the impact of care plan cessation for the elderly.